1991
DOI: 10.1007/bf00315986
|View full text |Cite
|
Sign up to set email alerts
|

Neuromodulators of the lingual von Ebner gland: an immunocytochemical study

Abstract: The serous lingual glands of von Ebner secrete lingual lipase, an enzyme that begins fat digestion in the stomach. The objective of this study was to characterize the neuromodulators in the rat tongue and von Ebner glands using immunocytochemical techniques. Rat lingual tissues were fixed in formalin, embedded in paraffin and sectioned at 4 microns for light microscopic studies. Immunocytochemical localization of neuromodulators was performed with monospecific anti-rat neuromodulator IgG or control (preimmune)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…DISCUSSION Our experiments showed that SP stimulated secretion of both lingual lipase and amylase from von Ebner's gland in a doseand time-dependent manner. In addition, recent histochemical studies of rat von Ebner's glands revealed degranulation of acinar cells in response to SP (53) and the presence of SP immunoreactivity in selective cells (38) and neuronal elements (33).…”
Section: Resultsmentioning
confidence: 99%
“…DISCUSSION Our experiments showed that SP stimulated secretion of both lingual lipase and amylase from von Ebner's gland in a doseand time-dependent manner. In addition, recent histochemical studies of rat von Ebner's glands revealed degranulation of acinar cells in response to SP (53) and the presence of SP immunoreactivity in selective cells (38) and neuronal elements (33).…”
Section: Resultsmentioning
confidence: 99%
“…Somatostatin, substance P, and vasointestinal peptide (VIP) have been localized immunohistochemically to nerve fi bers serving VEG (Roberts et al 1991); substance P fi bers were observed to be in close contact with myoepithelial cells (Oomori et al 1995). In general, secretion is controlled primarily by cholinergic stimulation with contributions from β -adrenergic stimulation and enhancement by substance P (Hamosh 1978, Field and Hand 1987, Field et al 1989, Gurkan and Bradley 1988, Ruellan et al 1988, Ueba and Uchihashi 1991.…”
Section: Lingual Serous Glands Of Von Ebner (Veg)mentioning
confidence: 94%
“…There are approximately eight to 12 circumvallate papillae, located directly anterior to the terminal sulcus. The ducts of the lingual glands of von Ebner secrete lingual lipase into the surrounding troughs to begin the process of lipolysis [10]. On the lateral surface of the tongue foliate papillae are identified, they are small folds of mucosa.…”
Section: Tongue Anatomymentioning
confidence: 99%